Association mapping and candidate gene identification for drought tolerance in sorghum - Min, Huiting; Wang, Kang; Wang, Tiantian; Cheng, Xinxiu; Habyarimana, Ephrem; Wang, Yongfei; Hu, Die; Wang, Yi-Hong; Wang, Lihua (Frontiers in Plant Science, 2025)
IntroductionWater is essential for plant growth, and drought is one of the most predominant constraints on crop yield. Sorghum is a well-known drought-tolerant crop model, and sorghum landraces possess novel alleles for local adaptation.MethodsIn this study, we evaluated a sorghum mini core panel of 239 landraces sampled globally for shoot and root growth under simulated drought conditions using 10% and 20% polyethylene glycol (PEG) in 2020 and 2024, and measured drought tolerance using the seedling tolerance coefficient (STC).Results and discussionPhenotypic analysis showed that more accessions produced more roots than longer roots when exposed to 10% PEG; however, at 20% PEG, more accessions produced longer roots than more roots, reflecting the adaptability of some accessions to drought stress. However, PEG reduced shoot growth in all accessions in both years. A genome-wide association study (GWAS) on 32 growth and 19 STC traits identified 22 loci, 19 of which were mapped to the STC traits, and 17 of these 19 were associated with STC of shoot weight. Eleven of the 22 loci were collocated with 23 previously identified mapped drought-related quantitative trait loci (QTLs); 15 of these 23 QTLs were mapped to green leaf area, total number of green leaves, or chlorophyll content. We also found 19 candidate genes for 12 of the 22 loci. Five of those genes showed either preferential or specific expression in the roots according to GeneAtlas v2. One candidate gene from a locus colocated with a previously mapped chlorophyll fluorescence QTL has been shown to increase chlorophyll fluorescence in maize in another study. The results of this study lay the foundation for further characterizing the sorghum mini core panel for novel drought-tolerant genes.